Eating our own Cooking:Toward a More Rigorous Design Science of Research Methods - Venable, John; Baskerville, Richard (Management Centre International Ltd, 2012)
This paper argues that Design Science is an appropriate paradigm for research into Research Methods. Research Methods (along with their tools and techniques) are purposeful artefacts, designed and created by people to achieve a specific purpose – i.e. to create new, truthful knowledge. Like other artefacts, research methods vary in their fitness to purpose, i.e. in their utility, depending on their fit and appropriate application to the particular purpose, contexts, and contingencies for which they were developed. Design Science Research aims at developing new purposeful artefacts with evidence of their utility. Applying a DSR perspective to research methods should yield increased utility in the application of research methods, better guidance in applying them and greater confidence in achieving the desired outcomes of applying them. Based on these premises, this paper reviews the basic concerns and issues in Design Science Research (using the balanced scorecard as an example purposeful artefact), then analyses the logical consequences of taking a Design Science perspective on research methods (using the Partial Least Square approach as an example research method purposeful artefact). First, it analyses the various purposes of research methods to clarify the alternative and competing design goals of research methods. Second, it analyses and characterises the types of purposeful (design) artefacts that comprise research methods. Third, it considers issues of the evaluation of research methods. Fourth and finally, it considered the development of design theories of research methods.